2019
DOI: 10.1007/s00401-019-02080-2
|View full text |Cite|
|
Sign up to set email alerts
|

4-Repeat tau seeds and templating subtypes as brain and CSF biomarkers of frontotemporal lobar degeneration

Abstract: To address the need for more meaningful biomarkers of tauopathies, we have developed an ultrasensitive tau seed amplification assay (4R RT-QuIC) for the 4-repeat (4R) tau aggregates of progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and other diseases with 4R tauopathy. The assay detected seeds in 10 6 -10 9 -fold dilutions of 4R tauopathy brain tissue but was orders of magnitude less responsive to brain with other types of tauopathy, such as from Alzheimer's disease cases. The analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 52 publications
4
105
0
Order By: Relevance
“…A key to success in developing RT-QuIC or other seed amplification assays is maximizing the kinetic difference between seeded and unseeded (spontaneous) polymerization of the substrate molecules. In our experience the K12CFh substrate is readily seeded but is less prone to spontaneous polymerization than the tau fragments that we have used in our previous tau RT-QuIC assays [21,23,28,29]. This feature can improve assay sensitivity and specificity, which may be crucial for detecting aggregates in accessible diagnostic specimens with relatively low tau seed concentrations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A key to success in developing RT-QuIC or other seed amplification assays is maximizing the kinetic difference between seeded and unseeded (spontaneous) polymerization of the substrate molecules. In our experience the K12CFh substrate is readily seeded but is less prone to spontaneous polymerization than the tau fragments that we have used in our previous tau RT-QuIC assays [21,23,28,29]. This feature can improve assay sensitivity and specificity, which may be crucial for detecting aggregates in accessible diagnostic specimens with relatively low tau seed concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Cysteines in the canonical tau sequences were mutated to serines (*) or alanine (★) for recombinant tau fragments used in tau RT-QuIC assays. The 3R, AD, and 4R RT-QuIC assays mentioned in this figure have been described previously [21,23,27,29] Table 1 End-point quantification of tau seeding activity in brain tissue across tau RT-QuIC assays fixed tissues were made using the stains described in [6,21]. Tissue samples in this study were collected from frontal cortex except for CTE and primary age-related tauopathy (PART) samples which were from temporal cortex.…”
Section: Neuropathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PMCA and RT-QuIC might be exploited for detecting peripheral disease-specific biomarkers associated with these more frequent disorders. In this regard, we and others have already shown that traces of aberrantly folded α-synuclein, amyloid-β, and tau can be detected in the cerebrospinal fluid and olfactory mucosa of patients with different neurodegenerative diseases [110][111][112][113][114][115][116][117][118][119]. However, these studies are in their very early phases of development and additional studies are required before these amplification technologies can be used as robust and reliable diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%